Post-Earthquake Fires (PEFs) in the Built Environment: A Systematic and Thematic Review of Structural Risk, Urban Impact, and Resilience Strategies - Fatma Kürüm Varolgüneş; Sadık Varolgüneş (Fire, 2025)
Post-earthquake fires (PEFs) represent a complex, cascading hazard in which seismic damage creates ignition conditions that can overwhelm urban infrastructure and severely compromise structural integrity. Despite growing scholarly attention, the literature on PEFs remains fragmented across disciplines, lacking a consolidated understanding of structural vulnerabilities, urban-scale impacts, and response strategies. This study presents a systematic and thematic synthesis of 54 peer-reviewed articles, identified through a PRISMA-guided screening of 151 publications from the Web of Science Core Collection. By combining bibliometric mapping with thematic clustering, the review categorizes research into key methodological domains, including finite element modeling, experimental testing, probabilistic risk analysis, multi-hazard frameworks, urban simulation, and policy approaches. The findings reveal a dominant focus on structural fire resistance, particularly of seismically damaged concrete and steel systems, while highlighting emerging trends in sensor-based fire detection, AI integration, and urban resilience planning. However, critical research gaps persist in multi-hazard modeling, firefighting under partial collapse, behavioral responses, and the integration of spatial, infrastructural, and institutional factors. This study proposes an interdisciplinary research agenda that connects engineering, urban design, and disaster governance to inform adaptive, smart-city-based strategies for mitigating fire risks in seismic zones. This work contributes a comprehensive roadmap for advancing post-earthquake fire resilience in the built environment.